Life in the Philosophy of Spinoza - Zac, Sylvain (Philosophy & theology, 1987)
The notion of life is here presented as a major theme which permeates all of Spinoza’s writings, from the earliest work to the mature statement of his philosophy in the Ethics. Some of the implications of this concept are here outlined, and a number of possible objections to my dynamic interpretation of the concept of life are also explicitated and answered. This artide is a translation of the essay, “Sur une idée directrice de la philosophie de Spinoza,” from Sylvain Zac, Etudes spinozistes, ©1985, Librairie Philosophique J. Vrin.